Pengaruh Fluktuasi Kurs Mata Uang terhadap Harga Saham Pt. Bank Central Asia, Tbk di Indonesia - Sheila Chairunnisa; Ahmad Prayudi (Economics, Business and Management Science Journal, 2022)
This research was conducted to measure the exchange rate (exchange rate) against stock prices at PT. Bank Central Asia, Tbk in Indonesia in 2018 and to find  how much these factors have an effect. The research method used was quantitative with associative techniques and simple linear regression. The sample in this study is the exchange rate and shares of PT. Bank Central Asia, Tbk in the monthly period throughout 2018. Data observation techniques are carried out using document observation techniques sourced from official website of Bank Indonesia (www.bi.go.id) as well as the official website of the Indonesia Stock Exchange (www.idx.co .id) for the share price. The results obtained show a significant value (sig) of XXX with a probability of The value of this value which is smaller than this probability indicates that there is an effect of currency exchange fluctuations on stock prices. Therefore, H0 is rejected and H1 is accepted. The conclusion of this study is that currency exchange rate fluctuations can affect stock prices by XX%.